Interactions between grassland birds and their snake predators: the potential for conservation conflicts in the Tallgrass prairie - Klug, Page Elizabeth (Kansas State University, 2009)
The loss, fragmentation, and degradation of grasslands have resulted in widespread declines in grassland birds. Nest predation is the leading cause of avian reproductive failure; therefore minimizing nest predation can lessen the severity of bird declines. Snakes are important predators of bird nests, but little is known about how snakes may enhance predation risk. To address this issue, I studied the habitat use, movement behavior, population genetic structure, and connectivity of snakes in the grasslands of northeastern Kansas. I addressed the connectivity of eastern yellowbelly racer (Coluber constrictor flaviventris) populations by using a landscape genetics approach at a broad scale (13,500 km2). I also radio-tracked the yellowbelly racer and Great Plains ratsnake (Pantherophis emoryi) at Konza Prairie Biological Station to understand their spatial ecology while simultaneously evaluating nest survival in grassland birds. Individual racers had limited dispersal (<3 km), but substantial admixture occurred within 30 km and populations were in migration-drift equilibrium and had high allelic diversity; therefore, racers must be abundant and continuously distributed for gene flow to be fluid throughout the region. Racers may be more likely to encounter bird nests, as they had more frequent movements and traversed greater distances on average than ratsnakes, which exhibited long periods of inactivity between directed movements. As for grassland birds, nest survival rates decreased with increasing shrubs and decreasing vegetation height. Discriminant function analysis revealed that successful nests were likely to occur in tall vegetation but reduced shrub cover, whereas higher shrub cover characterized snake habitats. Because snakes often use shrubs, nests in areas of increased shrubs may be at higher risk of predation by snakes. Targeted removal of shrubs may increase nest success by minimizing the activity of predators attracted to shrubs. Although predator removal is often a strategy for protecting bird populations, it may not be feasible in this instance, especially since snakes are a native component of the grassland community. Efforts to reduce snake predation on grassland bird nests should therefore focus on managing habitat within grasslands (i.e., shrubs) that influence snake activity, as no natural or anthropogenic habitat barriers currently limit snake movement across the landscape.
Keywords: Coluber constrictor; Pantherophis emoryi; Tallgrass prairie; Grassland birds; Predator-prey relationships; Nest predation; Agriculture, Range Management (0777); Biology, Ecology (0329); Biology, Genetics (0369)